Data mining and big data : second International Conference, DMBD 2017, Fukuoka, Japan, July 27-August 1, 2017. Proceedings /: second International Conference, DMBD 2017, Fukuoka, Japan, July 27-August 1, 2017. Proceedings. (2017) - Unknown
No abstract available